PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP CSR DISCLOSURE DAN IMPLIKASINYA TERHADAP EARING PER SHARE - Mita Septiani; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study examined the influence of firm characteristics to Corporate Social Responsibility Disclosure (CSRD) and the implications to Earning Per Share (EPS). This study was divided into two parts. The first part was to test the influence of  firm characteristics to the CSRD. The second part was to test the influence of the CSRD to EPS.This study used two regression models. The first regression model using multiple linear regression analysis that examined the effect of firm characteristics on the company CSRD. The second model using linear regression analysis that examined the effect of CSRD on EPS. The sample is annual report manufacture companies listed on the Indonesia Stock Exchange in 2010-2011.The results of this study indicate that in the first regression model, the characteristics of companies consisting of firm size and board of commissioners have a positive influence to CSRD that made by firm. Other variables consisting of profitability, level of leverage, management ownership and audit committee do not affect the CSRD. For the second model, CSRD have a positive effect to the earning per share.